Kajian Pengaruh Ukuran Bahan Biofil Trasi Terhadap Nilai pH dan Kadar BOD Dalam Pengolahan Limbah Cair Domestik - Muhammad Sulthon Djundy (Politeknik Amamapare, 2025)
This study aims to examine the effect of biofiltration material particle size on changes in pH and BOD values in the treatment of domestic household wastewater. Domestic wastewater generally contains organic materials that can increase BOD levels and cause pH imbalance, so a treatment process is required before being discharged into the environment. The study was conducted using a filtration method using a combination of bagasse, coconut shell charcoal, and zeolite media with particle sizes varying from 20, 40, and 70 mesh. The pH analysis was carried out using a pH meter, while the BOD value was measured using a DO meter. The results showed that the finer the particle size of the biofiltration media (larger mesh), the more effective the process of reducing pH and BOD values. The pH value after filtration was in the range of 7.9–8.3, while the BOD value decreased significantly from 153 mg/L to 33.9 mg/L. Although the BOD value does not fully meet the quality standards according to the Minister of Environment and Forestry Regulation No. 11 of 2025, these results indicate that the multi-media biofiltration system has potential as an environmentally friendly method for small-scale domestic wastewater treatment.